Sleep disorders during pregnancy - its prevalence, characteristic and neonatal implications - Sebastian Tomaszuk; Karolina Wąsik; Magda Wojtuś (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Each phase of a woman's life, from childhood to menopause, may be associated with a variety of sleep disturbances. The pregnancy is particularly predisposed to develop sleep disorders such as insomnia, restless legs syndrome and sleep-disordered breathing, which require special management. This article reviews the most common sleep disturbances in pregnancy and discusses epidemiology, pathophysiology, maternal and fetal possible implications and therapeutic options in the pregnant population.